THE IMPACT OF PLANT PESTS ORGANISM (OPT) AND CLIMATE CHANGE ON PRODUCTION AND INCOME OF BLACK RICE (Oryza sativa L. Indica) FARMERS IN SIRAMPOG DISTRICT BREBES REGENCY - Siti Mudmainah (Jurusan Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Mataram, 2025)
Black rice (Oryza sativa L. Indica) is a rice variety that contains the highest anthocyanin pigment. Sirampog Subdistrict is the only area in Brebes Regency that cultivates black rice. In 2017 to 2018, the amount of black rice production experienced fluctuating developments. The harvest area of ​​black rice farming in Sirampog Subdistrict is still fluctuating which affects production results. The results of black rice farming production that are still fluctuating indicate risks in black rice farming production, one of which is the presence of plant pest organism (OPT) and the impact of environmental changes that threaten to reduce the production and income of black rice farmers. The method used to determine respondents in this study is the census method, which involves taking the entire number of farmers as respondents, totaling 20 farmers. Black rice farming in Brebes Regency is a farming business cultivated in the Sirampog Subdistrict. Developed in five villages, namely Manggis Village, Mendala Village, Kaligiri, Sridadi and Mlayang Village. This study aims to analyze the effect of planting area, harvest area, OPT attack area, and the effect of flood area and drought area on lowland rice production in Sirampog Subdistrict. This research was conducted from January 2023 to October 2023. This study uses descriptive and quantitative analysis methods. Descriptive analysis is used to identify existing farmer data information sources and other supporting information obtained directly from interviews with black rice farmers. Quantitative analysis is used to evaluate the development of the main plant pest organisms (OPT) and the impact of environmental changes on black rice production in Sirampog Subdistrict, analyzed statistically with quantitative analysis with the help of the SPSS version 17 program. The analysis model that will be used is a multiple linear regression analysis model. The results of this study indicate an R2 value of 82.7% of black rice production and income are influenced by planting area (X1), harvest area (X2), attack area (X3), flood area (X4), drought area (X5) while 17.3% is influenced by variations in other variables outside the model (variables not studied). The income of black rice farmers is significantly affected by Rp. 37.157.560 per hectare in one harvest season.